UTILIZATION OF ANIMATION MEDIA IN LEARNER CHARACTER BUILDING - Selian, Bagas Nirwana; Zubaidah; Suraiya; Nurrahmi; Khalidillah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
This research aims to analyze the utilization of animation media in learner character building. The main focus of this research is to explore how animation media can be used as an effective learning tool in instilling positive character values among learners. This research uses a qualitative method with a literature study that collects and analyzes various relevant literature, articles, and previous research on the use of animated media in education. The sources used include scientific journals, books, and research reports that discuss the character of education and the use of animated media in the learning process. The results show that animation media has great potential in improving students' understanding of character values. This media is able to attract attention and increase learning motivation, as well as facilitate understanding of complex concepts through interesting visualizations. In addition, the use of animation media can also help learners internalize character values such as cooperation, responsibility, and empathy. Therefore, it can be concluded that the utilization of animation media in the character building of learners is effective and has a positive impact on the learning process. This study recommends that educators consider the integration of animation media in the education curriculum to enhance the learning process